Further evidence for a late locus of holistic word processing: Exploring vertex effect in the word composite task - Ventura, Paulo (2020)
Previous studies have shown a rather late and lexical level for holistic word processing. In the present study, we evaluated whether there are early effects in holistic processing of words, taking into consideration the role of lower-level visual processes that are critical in the hierarchy of visual word recognition: the extraction of viewpoint-invariant line junctions/vertices. We used contour-deleted words in two conditions: preservation of the vertices versus preservation of midsegments and an all-contour condition. We found evidence of a composite effect that was equivalent for all materials. Thus, we found no evidence of an early contribution of holistic processing to word recognition, and confirmed that holistic word processing is related to late lexical orthographic representations.